Analisis Deskriptif Pertumbuhan dan Perkembangan Cacing Tanah (Lumbricus rubellus) dengan Variasi Pakan Ampas Tahu dan Kotoran Sapi - Sari, Nurma Yunita; Koto, Irwan; Ruyani, Aceng; Yani, Ariefa Primair; Karyadi, Bhakti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Earthworms (Lumbricus rubellus) are beneficial invertebrates that reduce waste, animal feed, and cosmetic raw material. The research was conducted at Ruyani Life Sciences Learning Resources (SBIH), Bengkulu (Ruyani et al., 2018), from September to November 2023. The design of this study adopted a Complete Randomized Design (RAL) consisting of five experimental groups with different feed comparisons (in %).Earthworm growth and development are optimized in their natural habitat, which includes temperatures ranging from 15â„ƒ to 25â„ƒ, soil moisture and air availability between 15% and 30%, soil pH levels between 6.0 and 7.2, and the presence of organic matter for food. The study fed earthworms a diet consisting of tofu residues and cow dung in different proportions: (a) 100% tofu residues and 0% cow dung; (b) 75% tofu residues and 25% cow dung; (c) 50% tofu residues and 50% cow dung; and (d) 25% tofu residues and 75% cow dung. The research findings indicated that the ideal feed composition for maximizing earthworm biomass production is 25% tofu residues and 75% cow dung. Additionally, the most effective ratio of individual earthworms throughout a four-week maintenance period is 75% tofu residues and 25% cow dung.